2009
DOI: 10.1002/jobm.200900095
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of class 1 integrons in Aeromonas spp. isolated from human diarrheic stool in Mexico

Abstract: We determined the presence of class 1 integrons related to the acquisition of resistance to antimicrobials in Aeromonas spp. isolated from individuals with diarrhea. Species were identified as A. caviae, A. hydrophila, A. veronii and A. media using PCR-RFLP of the 16S rDNA. Selected isolates were further characterized by ERIC-PCR. Resistance to chloramphenicol, aztreonam, tetracycline, trimethoprim/sulfamethoxazole, nalidixic acid and streptomycin, among others, was determined using the Kirby-Bauer method. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…isolated from rainbow trout farms in Australia (Ndi and Barton 2011). However, the incidence of class 1 integrons in clinical samples has been documented by Pérez-Valdespino et al (2009), and there is a significant amount of information on class 1 integrons in animal faeces. Furthermore, the identification of class 1 and 2 integrase genes in mixed bacterial cultures enriched from bovine faeces has been previously documented (Barlow et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…isolated from rainbow trout farms in Australia (Ndi and Barton 2011). However, the incidence of class 1 integrons in clinical samples has been documented by Pérez-Valdespino et al (2009), and there is a significant amount of information on class 1 integrons in animal faeces. Furthermore, the identification of class 1 and 2 integrase genes in mixed bacterial cultures enriched from bovine faeces has been previously documented (Barlow et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Tetracycline resistance has been reported in Aeromonas species isolated from a river that receives wastewater discharge [25]. Similarly, Aeromonas hydrophila , Aeromonas caviae , and Aeromonas veronii isolated from human diarrhoeic stool in Mexico [26] showed variable resistances to tetracycline. Jacobs and Chenia [27] also observed high resistance to tetracycline in Aeromonas species from aquaculture system in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of class 1 integron may be attributed to a wide spread distribution of class 1 integron in Gram-negative microorganism. Pérez-Valdespino et al [26] reported presence of class 1 integron in Aeromonas species isolated from patient with diarrhoea in Mexico and found it had association with the acquisition of resistance to antimicrobials in Aeromonas species. The presence of class1 and 2 integron in Aeromonas and Enterobacteriaceae in Portugal was also reported [30, 31]; however higher prevalence of class 1 integron was found in final effluent [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…The resistance gene cassette aadA2 was previously described in Aeromonas spp. from humans in Mexico [32], Aeromonas spp. from rainbow trout in Australia [29], V. cholerae from human and environmental samples in Thailand [9] and S. enterica from food in Portugal [2].…”
Section: Discussionmentioning
confidence: 99%
“…Class 1 integrons is the most common integron type identified among resistant bacteria [32]. The elements could be horizontally transferred among bacteria inter-and intra-species and play an important role in the acquired resistance among Gram-negative bacteria [15].…”
mentioning
confidence: 99%